THE STRATEGY OF PESANTREN TO OVERCOME HOAXES (CASE STUDY IN PP. DARUL ULUM BANYUANYAR PAMEKASAN) - AR Samsul; Moh Busri (Fenomena, 2020)
Pesantren is always a solution for problems of the nation and state life. From the era of independence day until today, pesantren has become the frontline in responding to challenges and changing times. The rise of hoaxes makes people restless because their presence makes people feel scared, fragmented, and mutual hatred between each other. Pesantren is a place to learn religious sciences, and have a duty and responsibility to straighten and tackle the news hoax, especially the news hoaxes on behalf of Pesantren, or Kiai. This study examines the boarding school strategies for combating a hoax. This research is field research using a descriptive qualitative approach. Darul Ulum boarding Banyuanyar undertakes two strategies to combat the scams. The first emphasizes the use of social media, and the second is counter-narrative through sentries writing, which can then be distributed on social media. Furthermore, the steps taken to overcome the hoaxes are by holding workshops on the term hoaxes attack and establishing Banyuanyar Media Tim (BM TIM) as the solutions to overcome the hoaxes.